Environmental impact assessment : theory and practice - Mareddy, Anji Reddy (Elsevier Ltd. : Butterworth-Heinemann, 2017)
Environmental Impact Assessment: Theory and Practice describes the various pieces of knowledge necessary to speak the language of EIA and carry out EIAs focusing on a variety of environmental issues, including impacts on environmental components, like air, water, soils, land, noise and biological environments. Organized into 15 chapters, the book provides engineers with the tools and methods to conduct an effective assessment, including report preparations, design measures and relevant mitigation steps that can be taken to reduce or avoid negative effects. Case Studies are presented, providing guidance professionals can use to better understand, plan and prepare environmental impact assessments.